The Influence Of Occupational Safety and Health Training On Worker Safety Behavior at the UPTD Sungai Puar Community Health Center Batang Hari Regency Jambi - Humayroh; Rotua Sumihar Sitorus; Rahmad Gurusinga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Occupational Safety and Health (OSH) training is designed to enhance employees' understanding and awareness of potential hazards in the workplace, as well as to impart knowledge regarding safety standards, operational procedures, and the proper use of Personal Protective Equipment (PPE). This training plays a vital role in influencing behaviors related to occupational safety and health. The objective of this research was to investigate the impact of various factors—such as knowledge, educational background, disciplinary measures, regulations, support from supervisors, peer encouragement, availability of safety equipment, and duration of employment—on the safety practices of workers at the UPTD Sungai Puar Community Health Center in Batang Hari Regency, Jambi. Utilizing qualitative research methods, the study involved observations and interviews with 12 participants both prior to and following the training. The findings indicated that knowledge, education, disciplinary actions, regulations, support from superiors, peer motivation, availability of safety equipment, and tenure significantly affected the safety behaviors of the workers at the health center. Ultimately, the study concluded that education and support from supervisors emerged as the most significant determinants of Occupational Safety and Health behaviors.